POTENTIAL BIOSITES OF SIGNIFICANT IMPORTANCE IN LANGKAWI GEOPARK: TERRESTRIAL VERTEBRATE FAUNA - A., Norhayati; K.O, Chan; B., Daicus; L.L, Grismer; A., Mohd Izzudin (PLANNING MALAYSIA, 2011)
Langkawi Geopark was bestowed the status of a global geopark by the Global Geoparks Network (GGN) and endorsed by the UNESCO as the 52nd member of the GGN in 2007, making it the first in Malaysia and South East Asia to be given the status. The status is due to its many unique and significant geological, biological, and cultural features in Langkawi. There are four types of geoheritage conservation mechanism in Langkawi Geopark, namely geosites, geological monuments, landscapes of scenic beauty and Geoforest Parks. These proposed geoheritage conservation mechanisms are being implemented at various stages from planning to establishment and monitoring. So far, 97 geosites have been identified in Langkawi Geopark, but there has not been any biosite identified, even though Langkawi Geopark is known for the high biodiversity of flora and fauna, many of which are endemic and rare. This article highlights nine potential biosites for biological conservation in Langkawi Geopark. These biosites are identified based on the presence of rare and endemic species and/or based on type locality, which is the original location where the species was found and described. The nine biosites are Gunung Raya, Wat Wanaram, Lubuk Semilang, Telaga Tujuh, Pulau Singa Besar, Sungai Kilim/Kisap, Sg. Temurun, Gua Kelawar, and Teluk Datai. Each biosite is accompanied by description of the area, species, threats, conservation values, and potential for development and conservation measures. Although only nine biosites are identified so far, this number is bound to increase in future when more sites for the biologically important flora, invertebrate fauna and marine flora and fauna groups are included.